(untitled) - USMAN AFANDI, RICHO (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
As the changing of cultural values and the development era, businesses of food service are glancing coffee shop business, which is the attendance of coffee shop is the most appropriate lifestyles and trends of urban society today. As growed as businesses in the coffee shop area make the companies to create the advantage of their products remain competitive in this increasingly competitive. In addition, companies also need to create an atmosphere that supports the consumer in order to make them feel comfortable in that place. Comfortable atmosphere with unique decorated and creative is the main attraction for a cafe that makes consumers decide to visit the cafe and make purchasing decisions. The variables researched were the exterior (X1), interior (X2), and the layout / layout (X3) as independent variables and purchase decisions (Y) at Café Stillrod Surabaya as the dependent variable. This research used a questionnaire instrument and a sample of 302 respondents using multiple linear regression and processed using SPSS 16 for windows. Exterior (X1), interior (X2), and the layout (X3) at Café Stillrod Surabaya get Fcount 33,195 and 10,521 Tcount to the exterior; 2,189 for the interior; 3,202 for layout; 2,106 with a significance level of less than 0.05, so it can be concluded the influence simultaneously and partially between the exterior, interior, and layout on purchasing decisions on Stillrod Café Surabaya. Keywords: exterior, interior, and layout